"A Dark State of Affairs": Hajj Networks, Pan-Islamism, and Dutch Colonial Surveillance during the Interwar Period. (1st June 2014) - Alexanderson, Kris
Abstract: During the 1920′s and 30's, the Dutch colonial government worked together with the Dutch-owned shipping conglomerate Kongsi Tiga to control hajj maritime networks linking the Netherlands East Indies and the Middle East. This was a period of increasing Dutch anxiety over weakening imperial dominion in Southeast Asia and both the colonial administration and colonial businesses feared Muslim religious networks would expose colonial subjects to anti-imperial and pan-Islamic ideas while abroad. It was vital for Dutch shipping companies to maintain segregated and highly policed spaces onboard to uphold Kongsi Tiga 's monopoly over shipping between the Netherlands East Indies and Jeddah and to counter threats to Dutch hegemony more generally. Worried that "dangerous" passengers, such as Hadrami Arabs and Meccan sheikhs, would influence the general "spirit" of Indonesian pilgrims onboard by encouraging anti-colonial, nationalistic, and pan-Islamic sentiments, Kongsi Tiga systematically segregated passengers along racial, ethnic, and class lines. Racial and religious categories also informed Kongsi Tiga 's reactions to indigenous shipping initiatives by Indonesian Muslims. Proposals put forth by Muslim organizations such as Muhammidiyah, were swiftly undermined by the combined forces of Dutch shipping companies and the colonial administration who worked together to maintain a Dutch monopoly over hajj shipping, not only for financial profit, but to foster Dutch control over transnationally mobile colonial subjects. This article reveals the unique and vital role shipping companies played in expanding colonial politics, culture, and society across transoceanic spaces and reconceptualizes our geographic understanding of empire as inhabiting the overlooked oceanic spaces between metropole and colony.